PENGARUH TRAFFIC INTERNET SURFING TERHADAP PRESTASI BELAJAR BAHASA INGGRIS MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM - Permadi, Rudi (Program Studi Pendidikan Agama Islam, 2025)
This study was conducted to determine the effect of traffic internet surfing activities on English learning achievement. Experimentation acts as a method in this research. The data collection technique used tests. The sample in this study amounted to 40 students of the Islamic Education Study Program at the Tasikmalaya Institute of Islamic Religion. Random sampling technique was used as the sampling technique. The calculation of data analysis of this research shows that Asymp. Sig. (2-tailed) =0.000 less than Asymp. Sig. (2-tailed) < 0.05, which means that H0 is rejected, which means that there is an effect of internet surfing traffic activity on English learning achievement. In addition, the authors took other strength data from interviews. Future research is suggested to use other social media platforms besides WA Blast and also the moderation information content is not limited to flyers only. As a practical implication, the findings suggest the need for guidance for PAI students in utilizing the internet effectively to support English learning. It is important to balance the use of the internet for surfing activities with structured learning activities.